Survival estimates and outcome predictors in dogs with newly diagnosed diabetes mellitus treated in a veterinary teaching hospital. (7th December 2019) - Tardo, Antonio Maria; Del Baldo, Francesca; Dondi, Francesco; Pietra, Marco; Chiocchetti, Roberto; Fracassi, Federico
Abstract : Background: Diabetes mellitus (DM) is one of the most common endocrine disorders in dogs, but prognostic factors are still largely unknown. The aim of this retrospective, single‐centre, case series study was to determine overall survival time and identify the prognostic value of several clinical and clinicopathological variables in dogs with newly diagnosed DM. Methods: Cases of DM were identified within the electronic medical records of one referral centre. Sixty‐eight dogs with DM were included. Cox proportional hazards models were used to analyse variables associated with survival. Results: The median survival time was 964 days (range 22–3140). In multivariable model analysis, length of survival was significantly shorter for dogs with higher haematocrit value (hazard ratio (HR) 1.06, 95 per cent confidence interval (CI) 1.00 to 1.13) and higher serum phosphate concentrations (HR 1.83, 95 per cent CI 1.13 to 2.97). Serum phosphate concentrations were above the reference interval in 24 of 65 (37 per cent) dogs. Conclusion: Diabetic dogs have a good life expectancy. Hyperphosphataemia is a relatively common finding in dogs with newly diagnosed DM and represents a negative prognostic factor. The presence of pancreatitis might not be associated with an unfavourable outcome.